A comparative study to evaluate the efficacy of intrathecal dexmedetomidine and intrathecal clonidine as an adjuvant to hyperbaric 0.75% ropivacaine in patients undergoing orthopedic surgery under spinal anaesthesia - Sumedha Mehta; Jyoti Deshpande; Harsha Singhi; Arbaaz Pathan (Journal of Krishna Institute of Medical Sciences University)
Background: Spinal anaesthesia is a widely preferred technique for lower limb surgeries. Various adjuvants are used to prolong the duration and provide good postoperative analgesia. In our study, we compared the efficacy of intrathecal α-2-adrenergic receptor agonist, clonidine, and dexmedetomidine as an adjuvant to hyperbaric ropivacaine 0.75%. Aim and Objectives: To evaluate the efficacy of intrathecal dexmedetomidine and clonidine with hyperbaric ropivacaine 0.75% in orthopaedic surgeries. Material and Methods: The study was conducted in 100 patients of ASA I and II, randomly allocated in two groups (50 each) – 1) Group RC: 3.2 ml of intrathecal ropivacaine 0.75% heavy + 30 mcg of injectionclonidine, and; 2) Group RD: 3.2 ml of intrathecal ropivacaine 0.75% heavy + 3 mcg of injection dexmedetomidine. The drugs were compared based on the block characteristics, analgesic duration, 24-hour analgesic requirement, hemodynamic parameters, and side effects, if any. Results: Duration of sensory blockade (RC 268.98 ± 39.44 mins vs RD 288.62 ± 43.01 mins, p = 0.015) and motor blockade (RC 240.64 ± 39.93 mins vs RD 260.24 ± 39.30 mins, p = 0.011) was significantly prolonged in Group RD. The duration of analgesia was statistically significantly prolonged in Group RD 374.3 ± 30.06 mins vs Group RC 354.9 ± 32.21 mins, p = 0.005. There was significantly a greater 24-hour analgesia requirement in patients from Group RC (2.24 ± 0.59, p = 0.033). The side effects were comparable between the two groups. Conclusion: We recommend the use of intrathecal dexmedetomidine as an adjuvant in spinal anaesthesia as it prolongs the duration of sensory and motor blockade and provides good postoperative analgesia with hemodynamic stability and minimal side effects.